A family caregiver perspective: rethinking recovery with phenomenology - Ke, Junyu (Frontiers in Sociology, 2025)
Our phenomenal experience of the world is shaped by lived moments of the present, which not only sediment into the fabric of our current reality but also actively contribute to shaping it. We continually engage in the generative and rich making of life through this ongoing, dynamic interaction with the world. From this perspective, body–mind differences resulting from brain injury could be seen as a profound transformation of one’s phenomenal experience of the world. The lessons I have drawn from my caregiving experience with my sister who has critical brain injuries highlight the need to move away from ableist beliefs that disabilities are deficits to be corrected or rejected to a positive and generative search for the new, alternative ways of living well with shifted physio-psychological conditions. Using phenomenological perspectives, I aim to shift the understanding of “abnormality” from the binary of normal/abnormal to a broader vision of care. For family caregivers who struggle to help their loved one to return to a better state of health and life quality, the key point of participating in the recovery process is to gear into the lived experience of the care recipient and grasp a genuine understanding of their reality.